Development of an acceptable peanut milk yogurt - Bhogal, Sukhbir Kaur M. (College of Home Economics, University of the Philippines, 2013)
The goal of the study was to develop an acceptable yogurt product from peanut milk. To determine the optimum peanut milk yogurt formulation, a two-factor experimental design involving six formulations with varying amounts of evaporated milk and sugar was employed. Sensory evaluation conducted on a fifty-member panel showed that the most acceptable formulation contained 25% of evaporated milk and 10% sugar. Standardization of the product formulation and process was done using physicochemical analysis and sensory evaluation as parameters. All parameters tested showed no significant differences from the three production batches indicating that the goal of standardization was achieved. Results on the assessment of the physicochemical properties of the product showed an average pH of 4.69, titratable acidity (as % lactic acid) of 0.81% and apparent viscosity of 2,951 mPa-s. The pH and titrable acidity of the product both fell within the usual pH and titrable acidity ranges of milk yogurt, which indicates that it is safe and ready for consumption. The viscosity of the product was thinner compared to commercial yogurts. The peanut milk yogurt was also subjected to sensory evaluation including descriptive and acceptability tests. The parameters investigated yielded generally good acceptability from the panelists. The product was described as a cream-colored yogurt with a moderate consistency and a slightly distinct nutty flavor, which is moderately sweet and moderately sour.